(untitled) (Research, Society and Development, 2021)
This investigation aimed to evaluate the effectiveness of the participatory management of the Conselho Municipal de Educação - CME (Municipal Council for Education) of Mossoró from the perspective of relevant social actors, it is part of a set of research currently being carried out in Brazil on the impact of management councils on educational public policy. The quanti-qualitative research used an electronic questionnaire formulated in Google Forms, with a sample of 83.3% of respondents from the universe of 12 councilors of the 2016/2018 management of the CME of Mossoró-RN. We also proceeded with a structured interview with 4 councilors, in addition to a documentary survey and participation in meetings, fundamental aspects for a SWOT analysis of the Council, aiming also to point out prescriptions on the focal points of opportunities and improvements for participatory management. Based on the constructed indexes and the interviewees’ reports, we consider that the council’s general level of performance is “excellent” and “reasonable” as a joint, consultative, and deliberative space for the municipality’s public policies and educational demands.